2021
DOI: 10.1055/s-0041-1736544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Growth in Pediatric Syrian Refugee Populations in Jordan

Abstract: Background Externally displaced pediatric Syrian refugees are at risk of adverse developmental health outcomes in the setting of food insecurity. To evaluate the impact of displacement on nutritional status of Syrian children, this study describes the prevalence of malnutrition of Syrian children residing in Jordan. Methods A retrospective cross-sectional analysis of data from patient records < 18 years of age from the Syrian American Medical Society's (SAMS) January 2019 mission trip to Jordan wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The study conducted in Lebanon showed that the children most affected by malnutrition were between 0-1 years of age [8]. Acute malnutrition was most prevalent in children under the age of ve, according to a study done in 2019 among refugees living in camps [9]. According to UNICEF 2016 data, a moderate acute malnutrition was discovered in the refugee child as a result of the nutritional screening of more than 2200 Syrian refugee children.…”
mentioning
confidence: 99%
“…The study conducted in Lebanon showed that the children most affected by malnutrition were between 0-1 years of age [8]. Acute malnutrition was most prevalent in children under the age of ve, according to a study done in 2019 among refugees living in camps [9]. According to UNICEF 2016 data, a moderate acute malnutrition was discovered in the refugee child as a result of the nutritional screening of more than 2200 Syrian refugee children.…”
mentioning
confidence: 99%